Pengembangan Media Stik Es Krim Pada Materi Operasi Hitung dengan Metode Montessori Untuk Kelas II SD - Fajhriany, Aisyah Aulia; Ramadan, Zaka Hadikusuma (Cetta: Jurnal Ilmu Pendidikan, 2025)
Students' low understanding of arithmetic operations is caused by a lack of active participation during the learning process, leading to boredom and suboptimal engagement in lessons. To address this issue, interactive learning media that align with students' cognitive development stages are needed. This study aims to describe the development process, level of validity, and user responses toward the use of ice stick-based media employing the Montessori method for arithmetic operations material in Grade II at SD Islam Plus YLPI Pekanbaru. This is a development study using the ADDIE model, consisting of four stages: Analysis, Design, Development, and Implementation. The Evaluation stage was not conducted separately, as it was integrated into the validation and trial processes. The study involved two media expert validators, one Grade II teacher, and six Grade II students. Data were collected using expert validation sheets and teacher and student response questionnaires, which were analyzed both qualitatively and quantitatively. The results showed that the media achieved a very high level of validity, with a score of 94.1%. The teacher's response reached 100%, while the students’ response was 98.3%, indicating that the media is easy to use, engaging, and relevant to students’ learning needs. Therefore, the ice stick-based media is considered appropriate to be used as an interactive and enjoyable learning tool.